2006
DOI: 10.1111/j.1442-2042.2006.01220.x
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and characterization of human urothelial cancer xenografts in severe combined immunodeficient mice

Abstract: Aim : To establish and characterize a murine xenograft model of human urothelial cancer in severe combined immunodeficient (SCID) mice for therapeutic simulation. Methods : Pieces of 30 freshly resected urothelial tumors (24 obtained from bladder and 6 from ureter or pelvis) were implanted subcutaneously into SCID mice, and xenograft tumors were passed in tumorigenic cases. At each passage, histopathology, TP53 mutational status assessed by yeast p53 functional assay, and the Ki-67 labeling index (LI) were exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 17 publications
(19 reference statements)
1
21
0
Order By: Relevance
“…However, the extent of upregulation was not significantly different in chemosensitive and chemoresistant tumors. The detected chemosensitivity of HUH-PAS exclude resistance by unspecific selection processes in vivo , which might change cellular properties independently of therapeutic pressure [12,13]. …”
Section: Discussionmentioning
confidence: 99%
“…However, the extent of upregulation was not significantly different in chemosensitive and chemoresistant tumors. The detected chemosensitivity of HUH-PAS exclude resistance by unspecific selection processes in vivo , which might change cellular properties independently of therapeutic pressure [12,13]. …”
Section: Discussionmentioning
confidence: 99%
“…When analyzed, P53 expression and mutational status were found concordant between the original tumor and the xenografts. 23,28 On the other hand, Ki-67 index was increased in xenografts comparing with the original tumor, particularly after serial passages in mice. 23,25 These studies found no statistically significant relationship between success take rate and malignant characteristics of the original tumor (P53, Ki-67).…”
Section: Resultsmentioning
confidence: 93%
“…14,15,22 The studies that evaluated the xenografts after several passages confirmed the histologic stability of the xenografts in later passages. 12,22,23 The xenograft molecular characterization is summarized in Table III. Immunohistochemical assessment of xenografts was reported in 5 studies. The most frequently analyzed markers were P53 and Ki-67.…”
Section: Resultsmentioning
confidence: 99%
“…As far as we know, there were only three reports showing the presence of EBV in bladder tumors, including our previous work that lymphoproliferative disease (LPD) derived from EBV-infected tumorinfiltrating lymphocytes could occur when human bladder cancer materials were transplanted directly into severe combined immunodeficient (SCID) mice. 18 To date, it remains unknown whether EBV has a significant role in bladder cancer carcinogenesis. In the present study, we provide new evidence that there is an association between EBV and bladder cancer and indicate the possible role of EBV in bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, frozen material was available in 18 EBV‐positive cases. In the experiments, EBV lymphomas occurring in severe combined immunodeficient mouse xenotransplants were used as a positive control 18 …”
Section: Methodsmentioning
confidence: 99%